Pennsylvania and the Federal Constitution 1787-1788 - McMaster, John Bach, 1852-1932; Stone, Frederick D. (Frederick Dawson), 1841-1897 (Liberty Fund, 2011)
In their preface editors McMaster and Stone state that the "object of this book is to show the circumstances under which the Federal Constitution was ratified by Pennsylvania. She was the first of the large states to accept the plan that gave the states having a small population an equal representation in the Senate with the others, and her prompt action influenced the result." They note that "had this action been less prompt ... it would in all probability have caused the rejection of the Constitution." Using a wealth of primary documents, including the official proceedings and debates of the Assembly and the Convention, along with essays, squibs (short satirical news items), editorials, letters, speeches, and articles about the debates in Pennsylvania's ratifying convention, McMaster and Stone present both Federalist and Anti-Federalist viewpoints. In addition, they provide brief, noninterpretive editorial comments to give historical context to the discussion and include concise biographical sketches of key Pennsylvania figures during this crucial period of the American founding, such as Benjamin Franklin, Gouverneur Morris, Benjamin Rush, and James Wilson. McMaster and Stone point out that, twenty hours after the Continental Congress had submitted the new Constitution to the states, as a replacement for the Articles of Confederation, the Assembly of Pennsylvania called a convention to debate the proposed Constitution and to ratify or reject it. The passionate debate in favor of and against continued until Washington's oath of office as the first President of the United States